Optimizing performance nutrition for adolescent athletes: a review of dietary needs, risks, and practical strategies - Everett, S. (Nutrients, 2025)
Adolescent athletes face unique nutritional challenges due to the simultaneous demands of growth, development, and athletic performance. This review synthesizes current evidence on energy and macronutrient requirements, hydration strategies, and key micronutrients, including iron, calcium, and vitamin D, which are essential for supporting health and performance in youth sport. It explores the physiological risks associated with low energy availability (LEA), while emphasizing the importance of carbohydrate and protein timing, quality, and distribution. The review also evaluates the role of dietary supplements and ergogenic aids, including creatine and energy drinks, highlighting safety concerns and advocating for a food-first approach. Practical strategies for nutrition education, interdisciplinary collaboration, and individualized care are presented to guide healthcare professionals, coaches, and caregivers in fostering sustainable, performance-supportive eating habits. By aligning intake with training demands and developmental needs, adolescent athletes can optimize performance, recovery, and long-term well-being.